Erratum: Angular clustering of point sources at 150 MHz in the TGSS survey - Rana, S.; Bagla, J.S. (Oxford Academic, 2019)
We study the angular clustering of point sources in The GMRT (Giant Metrewave Radio Telescope) Sky Survey (TGSS). The survey at 150 MHz with δ > −53.5° has a sky coverage of 3.6π steradians, i.e. 90 per cent of the whole sky. We created subsamples by applying different total flux thresholds limit (Sflux ≫ 5σ) for good completeness and measured the angular correlation function ω(θ) of point sources at large scales (≥1°). We find that the amplitude of angular clustering is higher for brighter subsamples; this indicates that higher threshold flux samples are hosted by massive haloes and cluster strongly: this conclusion is based on the assumption that the redshift distribution of sources does not change with flux and this is supported by models of radio sources. We compare our results with other low-frequency studies of clustering of point sources and verify that the amplitude of clustering varies with the flux limit. We quantify this variation as a power-law dependence of the amplitude of correlation function with the flux limit. This dependence can be used to estimate foreground contamination due to clustering of point sources for low-frequency H i intensity mapping surveys for studying the epoch of reionization.
Keywords: Errata; Addenda Cosmology: large-scale structure of Universe; Observation